Simultaneous correlative scanning electron and high-NA fluorescence microscopy. - Nalan Liv; A Christiaan Zonnevylle; Angela C Narvaez; Andries P J Effting; Philip W Voorneveld; Miriam S Lucas; James C Hardwick; Roger A Wepf; Pieter Kruit; Jacob P Hoogenboom (PLoS ONE, 2013)
Correlative light and electron microscopy (CLEM) is a unique method for investigating biological structure-function relations. With CLEM protein distributions visualized in fluorescence can be mapped onto the cellular ultrastructure measured with electron microscopy. Widespread application of correlative microscopy is hampered by elaborate experimental procedures related foremost to retrieving regions of interest in both modalities and/or compromises in integrated approaches. We present a novel approach to correlative microscopy, in which a high numerical aperture epi-fluorescence microscope and a scanning electron microscope illuminate the same area of a sample at the same time. This removes the need for retrieval of regions of interest leading to a drastic reduction of inspection times and the possibility for quantitative investigations of large areas and datasets with correlative microscopy. We demonstrate Simultaneous CLEM (SCLEM) analyzing cell-cell connections and membrane protrusions in whole uncoated colon adenocarcinoma cell line cells stained for actin and cortactin with AlexaFluor488. SCLEM imaging of coverglass-mounted tissue sections with both electron-dense and fluorescence staining is also shown.